Vertebral hydatidosis: Surgical and medical treatment. About a case - Henderson, Eduardo; Reyes Cibils, José M.; Calegari, María (Cirugía del Uruguay, 1986)
Description and discussion of the medical history of a femaie patient with multiple antecedents in hydatidosis, affected by vertebral hydatidosis presenting medullar compression with paraparesis of lower extremities. She was thoroughly examined and operated twice, though stiil pendent the second stage of surgical treatment, consisting in the resection of two vertebral pieces. Operations were followed by evolutive control and medica! treatment with !he use of Mebendazol.